Al-Ittijah al-Ṣūfī wa al-Adab al-Sāmī fī al-Adab al-Indūnīsī al-Mu’āṣir - Nursomad, Nursomad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1999)
The article is a study on the strength of the sûfi elements in modern Indonesian literary discourse. Having explored the discourse on Sufism in the works of literature by the sûfi poets mentioned above, the article discusses the socio-political and religious context in which this transcendental literature emerged. And in this case there are at least twoDOI: 10.15408/sdi.v6i3.726